Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4236/arsci.2016.42008
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Pathophysiology and Medical Management of Endometriosis

Abstract: Endometriosis is an inflammatory oestrogen dependent disease defined by the presence of endometrial glands and stroma at extrauterine sites. The modern advance in treatment of endometriosis management is tackling the debilitating pain it causes, besides the infertility in patients desiring fertility in reproductive age group. This can be achieved by surgical or medical means, although in most cases a combination of both treatments is required. Usually, long term treatment is required in most cases. Unfortunate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 149 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…Endometriosis is an inflammatory disease caused by increased TNF-α and IL-1β, which reduce the protein expression of Bax and increase Bcl-2 to inhibit the apoptosis of endometriotic lesions [ 18 ]. A previous study indicated that FC inhibited inflammation and induced apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endometriosis is an inflammatory disease caused by increased TNF-α and IL-1β, which reduce the protein expression of Bax and increase Bcl-2 to inhibit the apoptosis of endometriotic lesions [ 18 ]. A previous study indicated that FC inhibited inflammation and induced apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Through macrophage or directly, estrogen can induce endometriotic-cell-secreted pro-inflammatory cytokines like tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6). When the inflammatory factor increases, the ability of anti-apoptosis, proliferation, invasion, and the migration ability is elevated in endometriosis cells [ 18 ]. In addition, TNF-α and IL-1β could induce NF-κB expression and further regulate vascular endothelial growth factor (VEGF) expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It not only reduces pain but also improves the microenvironment of adnexa and peritoneal, thereby increasing fertility. 1,2 Based on our results, those with endometriosis who underwent laparoscopic surgery had the rate spontaneous pregnancy of 46.3% within a year after surgery. 3 However, it should be noted that the recurrence rate increased within a year in the absence of pregnancy.…”
mentioning
confidence: 73%
“…3 However, it should be noted that the recurrence rate increased within a year in the absence of pregnancy. 1,4 Careful monitoring should be performed during the first year after surgery to increase the potency of fertility, and providing adjuvant hormonal therapy when necessary to reduce the risk of recurrence. 4,5 Medical treatment should be given for those who do not expect pregnancy to prevent recurrence.…”
mentioning
confidence: 99%